An integral membrane glycoprotein associated with an endocytic compartment of Trypanosoma vivax. Identification and partial characterization - Burleigh, B.A.; Wells, C.W.; Clarke, M.W.; Gardiner, Peter R. (Rockefeller University Press, 1993)
A 65-kD glycoprotein (gp65) of Trypanosoma (Duttonella) vivax was identified using a murine monoclonal antibody (mAb 4E1) that had been raised against formalin-fixed, in vitro-propagated, uncoated forms. Intracellular localization studies utilizing the mAb in immunofluorescence on fixed, permeabilized T. vivax bloodstream forms and immunoelectron microscopy on thin sections of Lowicryl K4M-embedded cells revealed labeling of vesicles and tubules in the posterior portion of the parasite. Some mAb-labeled vesicles contained endocytosed 10 nm BSA-gold after incubation of the parasites with the marker for 5-30 min at 37 degrees C, and the greatest degree of colocalization was observed after 5 min. Double labeling experiments using the mAb and a polyclonal anti-variant surface glycoprotein (VSG) antibody to simultaneously localize both gp65 and VSG demonstrated that there was little overlap in the distribution of these antigens. Thus, gp65 is associated with tubules and vesicles that are involved in endocytosis but which appear to be distinct from VSG processing pathways within the cell. Using the mAb for immunoblot analyses, gp65 was shown to be enriched in a fraction of solubilized membrane proteins eluted from either immobilized Con A or Ricinus communis agglutinin and was found to possess carbohydrate linkages cleaved by both endoglycosidase H and O-glycosidase, suggesting the presence of N- and O-linked glycans. Protease protection and crosslinking experiments suggest that gp65 is a transmembrane protein with trypsin cleavage and NH2-crosslinking sites on the lumenal face of the vesicles.